Algoritmisk aktiehandel med marknadsanalys via Reddit och Yahoo Finance - Enberg, Emanuel; Hagvall, Anton; Sköld, William; Söderholm, Adam; Zandhoff Westerlund, Viking; Öqvist, William (My University, 2021)
Algorithmic trading is becoming increasingly common in today’s digital society. We aim to investigate if algorithmic trading in combination with web scraping can yield a higher return than the market index, Dow Jones Industrial Average (DJIA). We have researched various inter- and intraday investment strategies, as well as analyzed the correlation between sentiment in Reddit comments on the one hand and news articles on the other hand, and stock prices. Here, we show that interday trading using the filter rule strategy performed better than DJIA, but also that no correlation was observed when sentiment analysis was performed on a small dataset utilizing our methods.
Keywords: investment; algorithmic trading; scraping; sentiment analysis; djia; reddit; yahoo